Pendampingan Keterampilan Berbahasa dengan Pendekatan Komunikatif-Integratif pada Siswa Panti Asuhan Anugerah Bengkayang Daerah Perbatasan - Jewarut, Siprianus; Kristianto, Aloysius Hari; Sumarni, Margaretha Lidya (Jurnal Pengabdian UNDIKMA, 2022)
This service program aims to improve language skills for elementary and junior high school students at Anugerah Bengkayang Orphanage in border areas. This program used an integrative communicative method with a pattern of mentoring. It was implemented during the 2-month service. The students who became the subject of mentoring were 21 students with details from 8 elementary schools and 13 junior high schools. The evaluation instrument for this activity was a questionnaire that was analyzed descriptively. The service activity results showed that the Anugerah Bengkayang Orphanage students were delighted with the mentoring program. Besides, four basic skills in language were well understood: Listening Skills, Reading Skills, Speaking Skills, and Writing Skills.